The Application of a New Porous High-Density Polyethylene Exogenous Scaffold in Nose Tip Shaping for East Asians - Liu, Jing; Meng, Xueyong; Liu, Jia; Chu, Tinggang; Zhang, Jun; Ma, Zhibing; Huang, Jinlong (Facial Plastic Surgery, 2025)
This study aimed to explore the clinical application value of a new porous high-density polyethylene (PHDPE, Supor) exogenous scaffold in nasal tip shaping for East Asians.We conducted a retrospective analysis of patients who underwent rhinoplasty involving the new nasal framework implantation at our institution from July 2020 to June 2024. Photographic measurement was used to obtain nasal-facial parameters, including nasal bridge length index, nasolabial angle, nasal tip projection, and the ratio of nasal tip width to nasal width, which served as objective indicators for nasal aesthetic evaluation. A rhinoplasty questionnaire was designed for patients to subjectively rate their nasal appearance, providing subjective indicators. The Nasal Obstruction Symptom Evaluation (NOSE) scale was utilized to assess nasal ventilation status, with the NOSE score as an indicator for nasal functional evaluation. Pre- and postoperative differences in nasal-facial parameters, self-rated nasal appearance, and NOSE scores were analyzed. The incidence of complications and patient satisfaction with surgical outcomes were also recorded. A total of 36 female Han Chinese patients with a mean age of 29 ± 4 years were included, with an average follow-up of 13 ± 4 months. Results showed that Nasal-facial parameters significantly improved postoperatively. The preoperative nasolabial angle was 102.9 ± 4.8 degrees, and the postoperative angle was 96.1 ± 2.8 degrees, with a significant decrease of 6.9 ± 2.2 degrees (p < 0.01). Only one patient developed a postoperative infection, while no other complications such as rejection, deformation, or implant extrusion were observed.In nasal tip plastic surgery for East Asians, the application of new PHDPE exogenous scaffolds yielded favorable surgical outcomes with low complication rates.
Keywords: nasal tip plastic surgery; porous high-density polyethylene materials; Supor implants; exogenous scaffolds